Analysis of periodontal status in Polish patients with rheumatoid arthritis treated with biological therapies - Joanna Samborska-Mazur; Dorota Sikorska; Marzena Liliana Wyganowska (Rheumatology)
Introduction Periodontitis, characterized by inflammation affecting the tooth-supporting tissues, may increase the risk of rheumatoid arthritis (RA) or cardiovascular diseases. The aim of the study was to evaluate the periodontal status in RA patients and its impact on the inflammatory markers and red cell parameters obtained from complete blood laboratory tests to study the risk of cardiovascular disease development.